The Effect of Competence and Job Placement on Employee Performance with Job Satisfaction as a Mediation Variable in the State Civil Apparatus (ASN) at the Regional Civil Service Agency of West Java Province - Dany Ika Yunica; Yenny Maya Dora (International Journal Labs, 2025)
Employee performance is not only seen at the top manager level, but must also be seen at the middle manager and subordinates or staff. If only top managers have high performance, then the quality of service perceived by the public will remain low. This is because the implementers in the field are actually staff. This research is quantitative verification research using the causality method with a survey approach. Researchers use all members of the population as research objects. The total population in the study was 131 employees of the Regional Civil Service Agency for the West Java Provincial Government. The analytical tools used in this research are SEM (Partial Least Square). The results of the research state that 1) Competency, Job Placement, Job Satisfaction and Employee Performance have good criteria at the Regional Civil Service Agency of West Java Province, 2) Competency has a positive influence on the performance of employees at the Regional Civil Service Agency of West Java Province, 3) Job Placement has a positive influence on the performance of employees at the Regional Civil Service Agency of West Java Province, 4) Job Satisfaction has a positive influence on employee performance at the Regional Civil Service Agency of West Java Province, 5) There is Competence on Employee Performance with job satisfaction as a mediating variable, 6) There is Job Placement on Employee Performance with job satisfaction as a mediating variable.